CT Fistulogram: Demonstration of Vasocutaneous Fistula, a Rare Complication Following Orchidectomy - Harshika Mittal; Senthil Kumar Aiyappan; Aishwarya V Athani (Journal of Clinical and Diagnostic Research, 2023)
A 65-year-old male patient presented with complaints of swelling and pain over the right inguinoscrotal region for the past two weeks. The patient had no significant previous medical history and no past surgical history. There was no history of vomiting or diarrhea. Local examination revealed a warm, tender swelling in the right inguinoscrotal region. Blood investigations showed neutrophilic leukocytosis with normal liver and renal function tests. An abdominal and scrotal ultrasound (USG) was performed, which revealed right epididymoorchitis with a multiloculated septated collection within the scrotal sac suggestive of pyocele. The spermatic cord structures were thickened, indicating funiculitis [Table/Fig-1]. The patient underwent a right high orchidectomy, and the postoperative period was uneventful. Histopathology of the specimen showed features of acute inflammation. Seven months following the surgery, he noticed a serous discharge from the right inguinal region with mild swelling and pain at the postoperative site. No definite spermatozoa were identified in the discharge. He was referred for a plain Computerised Tomography (CT) abdomen to the radiology department. Since there was a small opening in the right inguinal region from which discharge was seen, non-ionic water-soluble iodinated contrast was injected through the opening, and a CT fistulogram was performed. The CT fistulogram demonstrated contrast opacification of a tubular structure reaching up to the right seminal vesicle, suggestive of the vas deferens. Hence, a diagnosis of vasocutaneous fistula was made [Table/Fig-2]. Magnetic Resonance Imaging (MRI) screening was also performed, confirming the CT findings [Table/Fig-3]. The prostate and the rest of the abdominal organs were normal. The patient was advised to undergo surgery, and sinus tract excision was performed. The patient is doing well with no evidence of discharge at the postoperative site.